ナンキョク ツウシン ノ ゲンジョウ ト ショウライ ケイカク - 芳野, 赳夫; ヨシノ, タケオ; 福西, 浩; フクニシ, ヒロシ; Yoshino, Takeo; Fukunishi, Hiroshi (1985)
P(論文) 南極観測が開始されて以来, 昭和基地の運営は常に通信連絡によって支えられ今日に至っている。この間, 基地規模の拡大, 隊員増, 研究内容の充実, 前進基地の設置などに伴っていろいろな問題点が指摘され, また通信の内容も拡大の一途をたどってきた。したがって, 最初は短波によるA1,FAX, PIXが対内地通信の主流であったが, 通信量の増加に伴って必然的に急激な回線量の不足を招き, マリサット経由の衛星通信の実用化, 南極大陸内の通信網の確保と改善, 基地近くの通信の問題, 特に300-500kmの通信の問題点など, 今日解決すべき点が増してきている。本論文では南極通信の現状と将来の解決案などについて述べる。 The operation of Syowa Station has been maintained by the help of radio communications since 1957. The traffic capacity in Antarctica has increased rapidly due to the expansion of the station, increased members, substantial research items and establishment of advance stations. In the first decade, the A1 and A4 for PIX and FAX modulation system occupied the main stream of radio communication system between Syowa Station and Japan and the intra-Antarctic communications. But the increased traffic caused the shortage of circuit margin. The long distance bus link has to change the high speed PCM system through the geostationary satellites from HF link as if via Marisat. Much improvements are required in the following points : the intra-Antarctic system, the radiowave propagation between 300 and 500km, technical research on the local communication, and the data collection system of orbital satellites. The present situation and the future improvement of Antarctic communication are described in this paper. departmental bulletin paper